Temporal trends in management and outcomes of testicular cancer: A population‐based study. Issue 13 (16th April 2018) - Leveridge, Michael J.; Siemens, D. Robert; Brennan, Kelly; Izard, Jason P.; Karim, Safiya; An, Howard; Mackillop, William J.; Booth, Christopher M.
Abstract : BACKGROUND: Treatment guidelines for early‐stage testicular cancer have increasingly recommended de‐escalation of therapy with surveillance strategies. This study was designed to describe temporal trends in routine clinical practice and to determine whether de‐escalation of therapy is associated with inferior survival in the general population. METHODS: The Ontario Cancer Registry was linked to electronic records of treatment to identify all patients diagnosed with testicular cancer treated with orchiectomy in Ontario during 2000‐2010. Treatment after orchiectomy was classified as radiotherapy (RT), retroperitoneal lymph node dissection (RPLND), chemotherapy, or none. Surveillance was defined as no identified treatment within 90 days of orchiectomy. Overall survival (OS) and cancer‐specific survival (CSS) were measured from the date of orchiectomy. RESULTS: The study population included 1564 and 1086 cases of seminomas and nonseminoma germ cell tumors (NSGCTs), respectively. Among patients with seminomas, there was a significant increase in the proportion of patients with no treatment within 90 days of orchiectomy (from 56% to 84%; P < .001); the use of RT decreased over time (from 38% to 8%; P < .001); and the use of chemotherapy remained stable (from 6% to 9%; P = .289). Practice patterns 90 days after orchiectomy remained stable over time among patients with NSGCTs: from 51% to 57% for no treatment ( P = .435), from 43% to 43% for chemotherapy ( P = .336), and from 9% to 3% for RPLND ( P = .476). The OS rates for the entire cohort at 5 and 10 years were 97% and 96%, respectively; the CSS rates were 98% and 98%, respectively. There was no significant change in OS or CSS for patients with seminomas or NSGCTs during the study period. CONCLUSIONS: There has been substantial de‐escalation in the treatment of testicular cancer in routine practice since 2000. Long‐term survival in routine practice is excellent and has not decreased with the uptake of surveillance strategies. Cancer 2018;124:2724‐2732 . © 2018 American Cancer Society Abstract : In routine clinical practice, there has been an appropriate de‐escalation of testicular cancer treatment intensity since 2000. Survival rates expected from large centers or national programs have been maintained despite the setting and less intense treatment.